Evaluasi Kematangan Sistem Informasi Untuk Keselarasan Bisnis pada Perusahaan Manufaktur - Ignatius Novianto Hariwibowo; Clara Hetty Primasari; Chandra Hananto (Maranatha University Press, 2021)
This study aims to evaluate the alignment of the application of information technology (IT) with the company's business practices. This study uses COBIT 4.1. to assess the maturity of technology adoption and to explore factors that hinder the alignment of IT implementation with the business. The maturity level of technology application describes IT management in the company's overall business activities. The higher the maturity level, the clearer and more structured the role of IT and business will be. This research uses a case study method at PT. SAE (in Central Java Province). The result of this research is that PT. SAE has reached the defined process level. At this stage, the company already has standard IT management procedures, but not all business activities and not yet detailed. This problem is due to lack of strategic support from top management to achieve business goals with the help of IT. Therefore, the company needs to improve the function and role of the head of the IT department at PT. SAE.